Evaluasi Manajemen Risiko Teknologi Informasi Menggunakan Kerangka Kerja COBIT 5 (Studi Kasus Pada Perum Jasa Tirta I Malang) - M. Habibullah Arief; Suprapto Suprapto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The amount of contribution from telemetry system to support the main job of Perum Jasa Tirta I Malang on handling the flood prevention, making telemetry system as a vital system that must be spared from the risks. That risk might obstruct and effect the result of flood monitoring which potencially harmfull to society. Perum Jasa Tirta I Malang was established a policies about risk management, include managing the risk profile. An evaluation on the implementation of information technology risk management in Perum Jasa Tirta I Malang was done to measure the capability level accomplishment. Cobit 5 framework, especially in process domain EDM03 (Ensure Risk Optimisation) and APO12 (Manage Risk), was used as the basis of the evaluations, it turned out that capability level for both of process domain EDM03 and APO12 were on level 2. Target of capability level that want to be achieved by Perum Jasa Tirta I Malang for both of process domain EDM03 and APO12 are on level 3. In other words, the interval of deviation (gap) from the two domain process was 1. And then, risk identification was needed to figure out wether the current control was appropriated. Besides that, risk assessment was also needed to reduce impact and probability of the the risks. From the evaluation result, recomendation and mitigation strategy ware made to support the improvement for the implementation of risk management information and technology at Perum Jasa Tirta I Malang.